Pre-treatment of Teak Seed to Enhance Germination - Yadav, J. P. (Indian Forester, 1992)
Teak is the most extensively planted tree species is tbe State of Tripun, India. To hasten the slow process of germination pre-treatments of seed bave been recommended. Most common pre-treatments soaking and alternate soaking and drying were tested in nursery at Jamjuri, Tripura. The experiment was carried in Randomised Block Design witb ten treatments and six replications. The germination data were recorded on 30th, 46th and 70th day of sowing. Alternate soaking and drying stimulated quicker germination. However, tbe total germination was higher with the pre-soaking of seed in water for 144 hrs (six days) which is suitable under Tripura conditions.